Iodine and Thyroid Function Status, and Anti-thyroid Peroxidase Antibody among Pregnant Women in Eastern Nepal - Chaudhary, Lalit Narayan; Khatiwada, Saroj; Gelal, Basanta; Gautam, Sharad; Lamsal, Madhab; Pokharel, Hanoon; Baral, Nirmal (Journal of Nepal Health Research Council, 2017)
Background: Iodine deficiency, thyroid dysfunction and development of thyroid autoimmunity during pregnancy may affect mother and the developing fetus. This study was carried out to find iodine status, thyroid dysfunction and thyroid autoimmunity among pregnant women. Methods: Ninety two pregnant women from three districts of eastern Nepal (Sunsari, Morang and Jhapa) were enrolled for the study, and urine and blood samples were collected. Urinary iodine concentration (UIC), free thyroxine (free T4), thyroid stimulating hormone (TSH), thyroglobulin and anti-thyroid peroxidase (TPO) antibody levels were estimated. Results: The median UIC, mean free T4 and TSH, median thyroglobulin and anti-TPO antibody in the pregnant women were 282.2 (158.42-376) μg/L, 1.14±0.41 ng/dL, 4.57±2.56 IU/mL, 6.5 (4.0-11.0) ng/mL, 1.52 (0.97-2.23) IU/mL respectively. In sufficient (<150 μg/L), adequate (150-249 μg/L) and above requirements (250-499 μg/L) iodine intake was observed in 17 (18.5%), 22 (23.9%) and 53 (57.6%) women respectively. Subclinical hypothyroidism and overt hypothyroidism were seen in 18 (19.5%) and 1(1.1%) women, respectively. Elevated thyroglobulin (>40 ng/mL) and positive anti-TPO antibody was observed in three (3.26%) women for both. Conclusions: Iodine intake was sufficient among pregnant women recently, however, chronic iodine deficiency persisted in small fraction of pregnant women. Mild thyroid dysfunction was common, and thyroid autoimmunity was present in small portion of Nepalese pregnant women population. Keywords: Anti-thyroid peroxidase antibody; Iodine deficiency; Nepal; pregnant women; thyroid dysfunction.